Wastewater as a thermal resource: Exploitation strategies, design methodologies & prototype development - SPRIET, JAN LENNY (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2020)
The disruption of the climate was identified as one of nine planetary boundaries, and is one for which we are reaching the limits of safe operation on this planet. To that effect the European Commission launched the European Green Deal, aiming at transitioning the EU's economy towards increased sustainability. The research presented in this thesis subscribes to three of the main axes of this Green Deal: Increasing the EU's climate ambition. Supplying clean, affordable and secure energy. Building and renovating in an energy and resource efficient way. In the EU, heating and cooling account for around 50% of the energy consumption. 15-30% of thermal energy delivered to a building is still embedded in the wastewater when leaving the building, making it the largest source of energy loss in modern (passive and low--energy) buildings. For this reason, the EU, through a directive released in December 2018, officially recognised wastewater as a renewable source of energy. The research presented in this thesis aims at recovering the embedded heat in wastewater, and, on the one hand, to use it to reduce fuel requirements of the conventional heating system, thus reducing related costs and greenhouse gas emissions. On the other hand, it aims to use this embedded heat as a heat source for heat pumps, providing low--carbon, renewable heat. The research project focuses on three research questions (enumerated below), regarding the development and exploitation of recovering thermal energy from drain or waste water, called Drain Water Heat Recovery (DWHR). 1. How can DWHR contribute to the current heating mix, and to reaching emission reduction and renewable heating targets? 2. How do different situations in different sectors affect the design of DWHR systems? How can DWHR be implemented? 3. How can the current set of commercially available DWHR system be complemented or extended? To answer these questions the project assessed three different aspects from heat recovery from drain-- and wastewater: 1. The exploitation strategy: Where, within the water cycle, should heat be recovered from wastewater? 2. The design methodology: What are the differences in design for different sectors, different situations? 3. The prototype development: How can the current set of commercially available DWHR system be complemented and extended?
APPROVED
Keywords: Probabilistic method; Drain Water Heat Recovery; Wastewater and heat interaction; TEWI of domestic heating systems; Effluent Heat Recovery; Supply and demand interaction; wastewater treatment plants; District Heating; Hospitality sector; Kitchen Drain Water